Ionospheric measurements during the total solar eclipse of 11 August 1999 - Chandra, H.; Sharma, Som; Lele, P.D.; Rajaram, G.; Hanchinal, A.N. (My University, 2007)
A number of radio experiments were conducted at Ahmedabad (23°N, 73°E) with the aim of studying the ionospheric effects of the total solar eclipse of 11 August 1999. Rapid radio soundings from the ionosonde were made on the eclipse day and on control days. A riometer was operating at 30 MHz, and field strength measurements along the three oblique incidence paths of Colombo-Ahmedabad (11905 kHz), Bombay-Ahmedabad (558 kHz) and Rajkot-Ahmedabad (810 kHz) were also made. A reduction of about 20% was observed in the minimum frequency of reflection from the ionosonde (fmin), which indicates a reduction in D-region ionization. The critical frequency of the E-layer was not measurable beyond 1600 h IST on eclipse day due to the strong blanketing sporadic-E, but there is a 20% decrease in the critical frequency of the F1-layer. Although there was no change in the minimum virtual height of the F-layer on eclipse day, there appears to have been a decrease in the height of maximum ionization (hpF2) during the eclipse, indicating a reduction in the thickness of the F-layer. The signal strength of the Colombo-Ahmedabad path shows an initial rapid increase with the start of the eclipse (indication of a decrease in ionization in the D- and lower E-regions), but subsequently decreases until the maximum of the eclipse (excessive deviative absorption because of the wave penetrating to the E-region). The field strength measurements of the Bombay-Ahmedabad path show a large fading after sunset as the sky wave also appeared. On eclipse day the fading started about an hour earlier. Riometer recordings also show a higher signal during eclipse day, which again indicates an eclipse-associated decrease in ionization.
Keywords: Solar eclipse; Ionosphere; E-layer; F-layer